Complete genome of mangrove-derived anti-MRSA streptomycete, Streptomyces pluripotens MUSC 135T - Hooi-Leng Ser; Kok-Gan Chan; Wen-Si Tan; Wai-Fong Yin; Bey-Hing Goh; Nurul-Syakima Ab Mutalib; Learn-Han Lee (Progress in Microbes and Molecular Biology, 2018)
Microorganisms serve as attractive resources, owing to their ability to synthesize structurally-diverse substances with various bioactivities. Within the Bacteria domain, members of the genus Streptomyces have demonstrated remarkable ability to produce clinically useful, secondary metabolites such as anticancer, antioxidants, antivirals and antibacterials. Streptomyces pluripotens MUSC 135T was isolated as novel strain from mangrove forest in Malaysia. This strain exhibited broad spectrum bacteriocin against several pathogens including methicillin-resistant Staphylococcus aureus (MRSA) strain ATCC BAA-44, Salmonella typhi ATCC 19430T and Aeromonas hydrophila ATCC 7966T. Thus, the strain was selected for whole genome sequencing as an attempt to explore its bioactive potential. Here we report the first complete genome of S. pluripotens MUSC 135T genome which comprise of 7.35 Mbp with G+C content of 69.9 %. A total of 6,404 open reading frames (ORFs) were predicted, along with 18 rRNA and 69 tRNA genes. Using bacteriocin mining tool, BAGEL detected eights gene clusters associated with bacteriocin production including lanthipeptides and linear azol(in)e-containing peptides (LAPs). Members of Streptomyces have contributed greatly towards improving lives, particularly against deadly infections and chronic diseases. The availability of S. pluripotens MUSC 135T genome sequence has opened new window for drug discovery, particularly for effective drugs against harmful pathogens such as MRSA and certainly deserves further detailed study.